Pengaruh Kompetensi Profesional, Motivasi Kerja dan Optimisme Akademik terhadap Efektivitas Kinerja Guru SMK Negeri di Kabupaten Batu Bara - Marianum Marianum; Parulian sibuea; Syaiful Bahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of professional competence, work This study aims to determine the effect of professional competence, work motivation, and academic optimism on the effectiveness of teacher performance at SMK Negeri Batu Bara Regency. This research was conducted at Batu Bara District Vocational Schools, spread throughout the Batu Bara District, North Sumatra Province, with a total sample of 127 people. Data collection techniques using questionnaires and data analysis techniques, namely validity, reliability, t-test, and F-test. The results showed that there was an influence of professional competence (X1), work motivation (X2), and academic optimism (X3) together on the effectiveness of teacher performance where the calculated F value is 69,692 and a significance (Sig.) 0.000. The magnitude of the influence is indicated by the coefficient of determination R2 (R square) = 63.0, which means that Professional Competence (X1), Work Motivation (X2), and Academic Optimism (X3) jointly influence the Effectiveness of Teacher Performance by 630%. The remainder, 37.0%, is determined by other factors. In conclusion, there is a significant influence between professional competence, work motivation, and academic optimism on teacher effectiveness. Keywords: academic optimism, professional competence, work motivation